Enhancing Competitive Advantage: The Role of Learning, Integrating, and Recon-figuration Capabilities through Corporate Resilience - Yuanita Ratna Indudewi; Benedecta Nadya Evangelie (Master of Management, School of Business and Management, Petra Christian University, 2025)
This study aimed to provide strategic insights for small to medium-sized companies on enhancing their competitive advantage, especially by examining the corporate resilience reflected in their dynamic capabilities. Seventy-four business owners and managers in Surabaya are sample respondents in this research. Quantitative causal research aims to gain an in-depth understanding of the cause-and-effect relationship between companies' Learning Capabilities, Integrating Capabilities, and Reconfiguration Capabilities, and how these capabilities influence Corporate Competitive Advantage through Corporate Resilience. The mediation research employs SEM-PLS as a statistical analysis method. The observation of small to medium-sized corporate entities becomes interesting as we explore the respondents who predominantly come from the real estate sector. The result prevails that Integrating Capability and Competitive Advantage is significantly mediated by corporate resilience. However, Corporate Resilience does not considerably mediate the relationship between Learning Capability and Competitive Advantage. The findings provide a data-driven argument that the company's capability to acquire, assimilate, transform, and exploit knowledge does not directly affect corporate resilience and competitive advantage. The result triggers further discussion, which may be followed by future research based on the specific industry and the company's corporate culture.